Use of soybean fortified mixture among under-five malnourished children - N Dhandargi, Utalbasha; S Natekar, Deelip (International Journal of Nursing Research, 2023)
Malnutrition is one of the major health problems in developing and underdeveloped countries especially in children and it is inextricably linked with poor feeding practices and poverty. When the parents fail to meet the minimum daily requirement of nutritious food for their children it results into malnutrition. The poverty is the main culprit there is a need to adopt the cheap but highly nutritious foods as a supplement in their daily diet. Hence soybean fortified mixture is one of the best supplementary diets to fulfill the daily minimum nutritional requirement of the child and enhance appropriate growth and development. Soybean is a rich source of protein and its involvement in the diet with appropriate processing can have highly beneficent effects on the growth of the child. The aim of the study was to review the beneficent effects of using the soybean-fortified mixture for malnourished under-five children residing in the rural area. Dietary interventions include soybean-fortified mixture. Each dose/laado of Soya fortified mixture (contain roasted soybean flour, wheat flour and groundnut and jaggery) will give 14.09 gm of protein and 313.76 Kcal of energy. 200 gm of mixture given for one week into 4 divided doses gives 32.77 gm of protein and 727.25 Kcal of energy. Conclusion: The children below five years of age need the diet that is rich in protein and gives sufficient energy required for appropriate growth and development. Soybean fortified mixture used as supplementary diet is the best method to overcome the deficiency of protein among malnourished children.